Os viajantes e a escrita da economia animal no Brasil (Século XIX) (Revista de História Regional, 2025)
The article analyzes the importance of the so-called “four-legged economy” in the territorial integration and material life of Brazil from the colonial period to the Empire, highlighting the centrality of pack animals—mules, oxen, and horses—in the circulation of people, goods, and wealth. Based on the accounts of foreign travelers such as Langsdorff, Luccock, Saint-Hilaire, Spix and Martius, Henderson, Isabelle, and Dreys, it examines the conditions of muleteer routes, the dynamics of the Sorocaba fairs, the landholding and livestock structures of Rio Grande de São Pedro, as well as the supply of the mining regions and the Court in Rio de Janeiro. The study demonstrates how muleteering structured trade networks, consolidated routes, and fostered the emergence of towns and cities, functioning as a link between different regional economies. At the same time, it highlights the persistence of animal dependence, revealing the long duration of this system. The travelers’ diaries, though permeated by Eurocentric perspectives, constitute essential primary sources for understanding the internal circulation of animals, their economic and social implications, and the process of integrating the pastoral South into the rest of the Brazilian territory.
Keywords: Foreign travelers; Muleteering; Livestock; Territorial integration